Psychometric Evaluation of the Yale-Brown Obsessive-Compulsive Scale Modified for Body Dysmorphic Disorder (BDD-YBOCS) - Phillips, Katharine A. (2001)
The Yale-Brown Obsessive-Compulsive Scale Modified for Body Dysmorphic Disorder (BDD-YBOCS) is a semi-structured, clinician-rated measure of current BDD severity used in many BDD studies, but only one previous study has examined its psychometric properties. We examined the BDD-YBOCS’s psychometric properties in 200 BDD subjects from a prospective, observational study. Test-retest reliability (n = 64) and sensitivity to change with SRI treatment (n = 63) were examined in subjects from serotonin-reuptake inhibitor efficacy studies in BDD. Intraclass correlation coefficients demonstrated excellent interrater and test-retest reliability; internal consistency was strong. Principal components factor analysis identified two factors accounting for 66% of the variance. Analyses with measures of depression, social phobia, and global symptoms/psychosocial functioning indicated good convergent and discriminant validity. Mean BDD-YBOCS scores significantly decreased with treatment, indicating sensitivity to change. A ≥30% decrease in BDD-YBOCS score corresponded well to at least “much improved,” and ≥50% to “very much improved,” on the Clinical Global Impressions–Improvement scale. These results provide additional support for the BDD-YBOCS’s psychometric properties.